AmpliCoV: Rapid Whole-Genome Sequencing Using Multiplex PCR Amplification and Real-Time Oxford Nanopore MinION Sequencing Enables Rapid Variant Identification of SARS-CoV-2 - Brinkmann, Annika; Ulm, Sophie-Luisa; Uddin, Steven; Förster, Sophie; Seifert, Dominique; Oehme, Rainer; Corty, Merle; Schaade, Lars; Michel, Janine; Nitsche, Andreas (Frontiers in Microbiology, 2021)
Since the emergence of the Severe Acute Respiratory Syndrome Coronavirus-2 in December 2019, the scientific community is sharing data on epidemiology, diagnostic methods, and whole-genomic sequences almost in real time. The latter have already facilitated phylogenetic analyses, transmission chain tracking, protein modelling, the identification of possible therapeutic targets and a timely risk assessment. We have established and evaluated an amplification-based approach for whole-genome sequencing of SARS-CoV-2. It can be used on the miniature-sized and field-deployable sequencing device Oxford Nanopore MinION, with sequencing library preparation time of 10 min. We show that the sequencing of 24,000 total reads or > 21,295 SARS-CoV-2-specific amplicons in 46 min is sufficient for a near complete coverage (> 99 %) of the SARS-CoV-2 genome directly from patient samples even if virus concentration is low (Ct 32, corresponding to approximately 50 genome copies per reaction). For patient samples with high viral load (Ct 22), sequencing of 4,000 reads in 6 min was shown to be sufficient for a genome coverage of > 99 %. Comparison to Illumina data reveals an accuracy that suffices to identify virus mutants. AmpliCoV can applied whenever sequence information on SARS-CoV-2 are required rapidly, like for the identification of circulating virus mutants.